Migrasi Sebagai Upaya Penunjang Kehidupan Keluarga (Studi Terhadap Migran Sumba Timur Dalam Paguyuban Hikmast Di Kota Denpasar) - H. Djawa, Renais Rambu; Arjawa, I.G.P.B Suka; Punia, I Nengah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRACT Bali is one of the most famous tourism destination for both domestic and foreign tourists. The highly developed tourism sector of Bali has been able to attract entrants from everywhere around the world for various purposes either it’s pleasure, continuing education or also as an effort to support their family life as such done by migrants From East Sumba Regency in the province of East Nusa Tenggara (NTT) who gathered themselves in a community of East Suma called HIKMAST (Association of Families Matawai Amahu East Sumba) in Denpasar. Weak family life condition is the reason often found in addition to the lack of employment opportunity and wage inequality in the area of origin. This study use the qualitative descriptive method which aims to look at the driving reasons to migrate undertaken by migrants and the impact that is felt after migrating to Denpasar. In collecting the data, the authors use the technique of observation and semi-structured interviews that is also included in the category of in-depth interviews. Based on the research that has been done by using the theory of social action by Max Weber can be concluded that the migration has been able to support the migrants family life condition because it benefits various aspect such as economy, education, health, and psychological aspects of the migrants and their family. Kata Kunci : Migration, Migrants, East Sumba, Family Life Condition